Із спостережень над структурою щедрівок Волині - Панчук О. (Народна творчість та етнографія, 2005)
This article is dedicated to the winter folk calendar and special attention was paid to the Christmas Corals. Author is describing the most fundamental works dedicated to this topic previously beginning with O.Potebnya's studies. The typology, thematic variety, characters and personages of winter corals has been displayed and described in the article as well.